31.5k views
3 votes
Solve equations by applying the distributive property to simplify both sides of the equation if needed

-3(e+1)=2(e+11)
2k+6=3(2k-14)
8(x+3)= -4(2x-2)

User Scragz
by
8.1k points

1 Answer

2 votes

Final answer:

To solve the equations, apply the distributive property to simplify both sides of the equation if needed. Then, combine like terms and solve for the variable.

Step-by-step explanation:

To solve the equations, we need to apply the distributive property to simplify both sides if needed.

  1. -3(e+1) = 2(e+11)
  2. 2k+6 = 3(2k-14)
  3. 8(x+3) = -4(2x-2)

Let's solve each equation:

  1. -3(e+1) = 2(e+11)
    -3e - 3 = 2e + 22
    -3e - 2e = 25
    -5e = 25
    e = -5
  2. 2k+6 = 3(2k-14)
    2k + 6 = 6k - 42
    6 + 42 = 6k - 2k
    48 = 4k
    k = 12
  3. 8(x+3) = -4(2x-2)
    8x + 24 = -8x + 8
    8x + 8x = 8 - 24
    16x = -16
    x = -1

The solutions for the equations are: e = -5, k = 12, and x = -1.

User Houtman
by
6.5k points